Agreement, repeatability, and reproducibility of quantitative retinal layer assessment using swept-source and spectral-domain optical coherence tomography in eyes with retinal diseases - Hou, Huiyuan; Durbin, Mary K.; El-Nimri, Nevin; Fischer, Jeffrey L.; Sadda, Srinivas R. (Frontiers in Medicine, 2023)
Purpose: To evaluate the agreement and precision of retinal thickness measurements obtained using swept-source optical coherence tomography (SS-OCT) and spectral-domain OCT (SD-OCT) in healthy eyes and eyes with retinopathy. Methods: This cross-sectional prospective study involved three DRI-OCT Triton (SS-OCT) and three 3D-OCT-1 Maestro (SD-OCT) devices. One of each device (Maestro and Triton) was paired with a single operator. Healthy subjects and patients with retinal diseases were recruited, with study eye and testing order randomized. At least 3 scans per eye were captured for Wide scan (12mm×9mm- Triton and Maestro) and Macular Cube scan (7mm×7mm- Triton; 6mm×6mm- Maestro). Thickness of the full retina, ganglion cell layer + inner plexiform layer (GCL+), and ganglion cell complex (GCL++) were obtained from Wide scan and Cube scans. Agreement of the measurements between the Triton and Maestro was evaluated by Bland-Altman analysis and Deming regression for each group. Repeatability and reproducibility were assessed using a two-way random effect analysis of variance (ANOVA) model for each parameter by group. Results: 25 healthy subjects (25 eyes) and 26 patients with retinal diseases (26 eyes), including, but not limited to, age-related macular degeneration, macular hole, and diabetic retinopathy were recruited. Overall, the measurement differences between Triton and Maestro were <6µm (mean differences of full retina, GCL++, and GCL+ thickness were ≤5.5µm, 1.3µm, and 2.8µm, respectively) and not statistically significant across the parameters. The repeatability and reproducibility estimates indicate high precision in both devices and groups. Across all the parameters, the repeatability limit was ≤7.6µm for Triton and ≤12.7µm for Maestro; reproducibility limit was ≤9.2µm for Triton and ≤14.4µm for Maestro. In eyes with retinal pathology, the repeatability coefficient of variation (CV)% was ≤2.6% for Triton and ≤3.4% for Maestro; reproducibility CV% was ≤3.3% for Triton and ≤3.5% for Maestro. Conclusion: Both Triton SS-OCT and Maestro SD-OCT provide reliable measurements of retinal thickness in healthy eyes and eyes with retinal diseases. Excellent agreement between the two devices indicates interoperability when testing healthy eyes or eyes with retinal pathology. These findings support the use of thickness measurements from Triton SS-OCT and Maestro SD-OCT in clinical practice.